AB0973 Temporomandibular Joint Arthroscopy in Juvenile Idiopathic Arthritis. Successfully Treatment with Synovial Electrocoagulation. (9th June 2015) - Iglesias, E.; Cho, G.-Y.; Inarejos, E.; Bou, R.; Navallas, M.; Rodríguez, N.; Sánchez-Manubens, J.; Torrente-Segarra, V.; Calzada, J.; Antόn, J.
Abstract : Background: Temporomandibular joint (TMJ) is affected in approximately 80% of Juvenile Idiopathic Arthritis (JIA) patients, usually asymptomatic. Magnetic Resonance Imaging (MRI) with contrast remains as the gold standard for its diagnosis. Main objectives of management are to control active synovitis and prevent chronic damage but nowadays there is not a consensus on how to treat these patients. TMJ arthroscopy seems to be a non-invasive technique that allows direct examination and local treatment. Objectives: To review our JIA patients who have been treated with TMJ arthroscopy because of local active synovitis. Assess clinical and MRI with contrast outcome after 6 and 12 months. Methods: We made a retrospective charts review of our JIA patients in whom TMJ arthroscopy had been done. Clinical symptoms and signs were evaluated as pain, maximum interincisal opening, mouth opening deviation and/or presence of microretrognatia. MRI with contrast of TMJ was done before and after arthroscopy. Activity and damage was evaluated with Cron et al score. Arthroscopy was made under general anesthesia and nasotracheal intubation. We used a 1.9 mm glass lens arthroscope for small joints. If synovitis was detected local electrocoagulation was done. We made local infiltration with 1 ml of triamcinolone hexacetonide and sodic hialuronidate. Results: 12 patients were included. Clinical symptoms and imaging score improved after arthroscopy in all patients. We have not complications. Not local relapse have been identified. Conclusions: TMJ arthroscopy is a complex technique that allows direct joint examination. Electrocoagulation produces a synovial scar that reduce relapse with low index of complications. This technique seems to be promising in patients with TMJ active synovitis despite of systemic treatment. References: Stoll ML, Sharpe T, Beukelman T, Good J, Young D, Cron RQ. Risk factors for temporomandibular joint arthritis in children with juvenile idiopathic arthritis. J Rheumatol 2012;39(9)1880-87 Vaid YN, Dunnavant FD, Royal SA, Beukelman T, Stoll ML, Cron RQ. Imaging of the temporomandibular joint in juvenile idiopathic arthritis. Arthritis Care Res 2014;66(1):47-54 Disclosure of Interest: None declared